Where Do the New U.S. Immigrants Live? - Bartel, Ann P. (Journal of Labor Economics, 1989)
"Analyzing the location choices of the post-1964 U.S. immigrants results in three main findings: (1) these immigrants are more geographically concentrated than natives of the same age and ethnicity and reside in cities with large ethnic populations; (2) education plays a key role in location choice, reducing geographic concentration and the likelihood of being in cities with a high concentration of fellow countrymen and increasing the probability of changing locations after arrival in the United States; (3) internal migration within the United States occurs more frequently among immigrants than natives and facilitates the process of assimilation for the more educated individuals."